Isolation and characterization of saprophytic and pathogenic strains of Leptospira from water sources in the Midwestern United States - Hamond, Camila; LeCount, Karen; Anderson, Tammy; Putz, Ellie J.; Stuber, Tod; Hicks, Jessica; Camp, Patrick; van der Linden, Hans; Bayles, Darrell O.; Schlater, Linda K.; Nally, Jarlath E. (Frontiers in Water, 2024)
The genus Leptospira is a diverse and unique group of bacteria comprising multiple saprophytic and pathogenic species, which survive and persist in suitable moist environments. Pathogenic species cause human and animal leptospirosis, a global and neglected zoonotic disease. Disease transmission occurs by exposure to contaminated water and moist soil environments, or by contact with domestic animals and wildlife acting as reservoir hosts that shed Leptospira via urine. Here, we describe the unexpected diversity of saprophytic and pathogenic species of Leptospira isolated from water in the Midwestern United States. Samples were collected by volunteers in eleven counties in Iowa from water sources including puddles, sewage, creeks, ponds, lakes, and rivers during the summer of 2021. One hundred and five water samples were tested by culture for the presence of saprophytic and pathogenic species, and by lipL32 qPCR specific for the detection of pathogens; 82 (78.1%) were culture positive and five (4.8%) were positive by lipL32 qPCR. Whole genome sequencing of isolates cultured from water samples identified ten species of saprophytes including L. montravelensis, L. kemamanensis, L. bandrabouensis, L. bourretii, L. bouyouniensis, L. chreensis, L. ellinghausenii, L. terpstrae, L. yanagawae, and L. abararensis, as well as three novel saprophytic species. Whole genome sequencing also identified two novel pathogenic species. The remaining cultures comprised mixed populations of saprophytic species, as well as six that comprised a mixture of saprophytic and pathogenic species. One of these mixed cultures was enriched to select for a clonal isolate of pathogenic Leptospira, strain WS101.C1, which was classified as L. interrogans serogroup Djasiman serovar Djasiman. Cumulatively, 9.5% (10/105) of water samples were positive for pathogenic Leptospira. This work emphasizes the diversity of Leptospira present in water sources in the Midwestern U.S. and provides unique opportunities to explore the geographic diversity and evolution of this genus. The identification of known and novel pathogenic species circulating in local water sources highlights their potential usefulness as diagnostic antigens, as well as the role of water in transmission of infection to human and animal populations. Integrating knowledge on human, animal, and environmental health is essential to control and predict risk for zoonoses.